Depression and Anxiety Disorders in Patients With Inflammatory Bowel Disease - Hu, Shurong; Chen, Yiping; Chen, Yan; Wang, Caihua (Frontiers in psychiatry, 2021)
Mental health is a significant yet overlooked aspect of inflammatory bowel disease (IBD) patient care, with challenges in determining optimal treatments and psychological health resources. The most common psychological conditions in patients with IBD are anxiety and depression. The increased prevalence of these mental disorders appeals to mental screening of each person diagnosed with IBD at initial consultation. There are simple and clinically viable methods available to screen for mental problems. Psychological methods may be as or even more significant as a therapeutic modality. Herein we discuss the three major areas of psychological co-morbidity in IBD: (1) the prevalence and risk factors associated with anxiety and depression disorders for patients with IBD; (2) diagnosis of psychological disorders for patients with IBD; (3) treatment with patients with IBD and mental disorders. The gastroenterologists are encouraged to screen and treat these patients with IBD and mental disorders, which may improve outcomes.